STUDI EKSPERIMENTAL PERFORMANSI TURBIN SAVONIUS DI PESISIR PANTAI KABUPATEN DEMAK TERHADAP DAYA LISTRIK YANG DIHASILKAN - Wahyu Santoso; Herman Saputro; Husin Bugis (Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2021)
Energy from fossil fuels consisting of petroleum, coal, natural gas containing raw material for energy fulfillment in Indonesia is still very central through the use of raw materials from renewable energy is still very low. In Indonesia the potential for renewable energy such as wind energy needs to be optimized. One of the uses of wind energy is through savonius wind turbine as electricity generators. Characteristics of savonius wind turbine with vertical axis rotors which gave a simple shape, and that able to control low speeds. This is in accordance with regions in Indonesi which have low average speeds.         This experimental study, aims to determine the description of wind potential and determine the performance of savonius wind turbines on the coast of Demak regency on the electrical energy produced. Savonius wind turbine used is made of galvalum material in the form of an S type rotor with diameter 1.1 m and height 1.4 m, using pulley transmission system with multiplication ratio 1:6 dan using generator type PMG 200 W. This research uses the method experiment. Data collection in the form of wind speed, humidity, temperature, rotor rotation speed, voltage and electric curret is carried out at 14.30 to 17.30 Western Indonesian Time. Data Analysis in this study uses quantitative descriptive analysis. The result showed the potential of wind on the coast of Demak regency have an average wind speed of 2,02 m/s with a temperature of 31,34 0C and humidity of 76,96. And the performance of the installed wind turbine produces the highest power 3.5 watt with an electric power coefficient of 0,181 and tip speed ratio around 1,75. From these result, the potensial of wind with performance savonius turbine can generate electricity used for pond lighting in the village Berahan Kulon Kecamatan Wedung.